Photo-thermal response self-healing coating and preparation method thereof
By introducing photothermal response MXene@EVA material into the self-healing coating, the self-healing process is triggered by near-infrared radiation, the problem of low self-healing efficiency in the prior art is solved, and efficient damage healing and anti-corrosion effects are achieved.
Patent Information
- Application Number
- CN202510071390.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-16
- Publication Date
- 2025-04-18
AI Technical Summary
The existing self-healing coatings have low repair efficiency under service conditions, and the self-healing process of polymer coatings and the interface corrosion process of substrates are a coupling and competition relationship, affecting the repair performance.
Using a photothermal triggering repair strategy, MXene@EVA material is formed by dispersing MXene in water and dispersing EVA microspheres in DMF, and mixed with aqueous resin, polypropylene glycol diglycidyl ether and curing agent, and applied to the substrate surface to achieve the preparation of a photothermal response self-healing coating.
Under near-infrared radiation, the coating can quickly heat up, initiate the shape memory process, promote crack closure, and the phase transition of EVA microspheres from solid to liquid fill the damaged part, achieving efficient damage healing and significantly improving the anticorrosion effect.
Smart Images

Figure CN119842290A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of anti-corrosion coatings, and in particular relates to a photothermal response self-healing coating and a preparation method thereof. Background Art
[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.
[0003] The impact of coating defects on its service life is crucial. Organic coatings often serve in harsh environments and are inevitably subject to severe damage such as physical damage. Composite coatings with corrosion inhibition functions can no longer meet the needs of repairing larger coating defects. Compared with composite coatings with corrosion inhibition functions, self-healing or self-repairing anti-corrosion coatings (SHACs), as a class of smart materials, can actively respond to external stimuli, automatically repair coating defects, and effectively restore the protective function of the underlying substrate. Embedding containers or capsules into coatings has been shown to effectively inhibit localized corrosion. However, many encapsulated repair agents including dicyclopentadiene, linseed oil, alkoxysilanes, tung oil, silyl esters, and isocyanates are liquids at room temperature and are unstable in actual anti-corrosion coatings.
[0004] In the current technical solution using solid repair agents, a SHAC based on ethylene-vinyl acetate requires artificial heating of the entire coating to achieve self-repairing effects, which is not convenient in actual environments. In addition, the self-repair process of the polymer coating and the interfacial corrosion process of the substrate are coupled and competitive. It is reported that the rate of oxygen reduction reaction on the metal surface is almost instantaneous, and its process will compete with the repair process and limit the repair performance of SHAC. Summary of the invention
[0005] In order to address the deficiencies of the prior art, the purpose of the present invention is to provide a photothermal responsive self-healing coating and a preparation method thereof, which adopts a repair strategy based on photothermal triggering to solve the problem of low repair efficiency of the self-healing coating under service conditions.
[0006] In order to achieve the above object, the technical solution of the present invention is:
[0007] In a first aspect, the present invention provides a method for preparing a photothermal responsive self-healing coating, comprising the following steps:
[0008] S1, dissolving an EVA copolymer having a melting temperature of 70 to 80° C. in chloroform to form a polymer solution having a concentration of 15 to 60 mg / mL, dripping the polymer solution into an aqueous solution of 0.5 to 1.0 wt % sodium dodecyl sulfate, and continuously stirring until the chloroform evaporates to obtain EVA microspheres;
[0009] S2, dispersing MXene in water to obtain a first mixed solution with a concentration of 2 to 5 mg / mL, and dispersing EVA microspheres in DMF to obtain a second mixed solution with a concentration of 1 to 4 mg / mL; mixing and stirring the first mixed solution and the second mixed solution in a volume ratio of 1:(1 to 2), and then filtering, washing and drying the product to obtain a MXene@EVA material;
[0010] S3. After mixing 30 to 40 parts by mass of an aqueous resin, 6 to 9 parts by mass of polypropylene glycol diglycidyl ether PPGDGE and 10 to 15 parts of a curing agent, 1 to 5 parts by mass of MXene@EVA material are added under continuous stirring conditions. After being evenly dispersed, the mixture is coated on the surface of the substrate and cured at 20 to 40°C to obtain a photothermal responsive self-healing coating.
[0011] Optionally, in S1, the method of continuous stirring is: continuously stirring at a stirring speed of 1000 to 1500 rpm for 24 to 48 hours at room temperature.
[0012] Optionally, in S1, the aqueous solution of sodium dodecyl sulfate containing EVA microspheres is filtered to obtain EVA microspheres, and the EVA microspheres are washed with deionized water and then dried at room temperature.
[0013] Optionally, in S2, MXene is selected from one or more of Ti3C2, V2C and Nb2C.
[0014] Optionally, in S2, MXene is ultrasonically dispersed in deionized water for 10 to 15 minutes to obtain a first mixed solution.
[0015] Optionally, in S2, the EVA microspheres are placed in DMF and ultrasonically dispersed at room temperature for 10 to 30 minutes to obtain a second mixed solution.
[0016] Optionally, in S2, after the first mixed liquid and the second mixed liquid are mixed, stirring is continued at a stirring speed of 500 to 700 rpm for 24 to 48 hours.
[0017] Optionally, in S2, the drying process is performed at room temperature.
[0018] Optionally, in S2, the MXene@EVA material obtained is in the form of microspheres with a size of 50 to 80 μm.
[0019] Optionally, in S3, the water-based resin is selected from one or more of polyurethane, acrylate and epoxy resin.
[0020] Optionally, in S3, the curing agent is selected from one or more of polyamide and polyetheramine.
[0021] Optionally, in S3, MXene@EVA material is added under continuous stirring conditions, and a viscous mixture is obtained after ultrasonic dispersion, and the viscous mixture is evacuated for 10 to 15 minutes.
[0022] Optionally, in S3, the substrate is a metal substrate, including: one of steel and nonferrous metal.
[0023] In the second aspect, a photothermal responsive self-healing coating is prepared by the preparation method of the above-mentioned photothermal responsive self-healing coating, the coating thickness is 70 to 100 μm, and MXene@EVA material microspheres with a size of 50 to 80 μm are uniformly dispersed in the coating.
[0024] In a third aspect, the preparation method of the above-mentioned photothermal responsive self-healing coating and / or the application of the above-mentioned photothermal responsive self-healing coating include: application on the surface of vulnerable parts in marine equipment.
[0025] The beneficial effects of the present invention are:
[0026] The polypropylene glycol diglycidyl ether PPGDGE in the coating acts as a soft segment to impart shape memory effect to the polymer matrix. Under near-infrared radiation, thanks to the excellent photothermal conversion ability of the MXene material, the photothermal responsive self-healing coating can quickly heat up to start the shape memory process of the coating matrix and promote crack closure. At the same time, the microspherical EVA material undergoes a phase change from solid to liquid, further filling the damaged part of the coating to complete the crack healing process. More importantly, the MXene nanosheets dispersed in the resin matrix can play a physical barrier role, produce a "maze effect" and thus prolong the penetration time of the electrolyte. The synergistic effect makes the synthesized smart coating have efficient damage healing ability and show anti-corrosion effects in practical applications. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.
[0028] Figure 1 These are scanning electron microscope images of the EVA microspheres and the EVA microspheres loaded with MXene nanosheets in Example 1 of the present invention; (a) is an image of the EVA microspheres, and (b) is an image of the EVA microspheres loaded with MXene nanosheets.
[0029] Figure 2 It is a real-time temperature change curve diagram of the coating prepared under five near-infrared laser on / off cycles in Example 1 of the present invention and Comparative Example 1.
[0030] Figure 3are images of the self-healing effect of the damaged coatings in Example 1 and Comparative Example 1 of the present invention after being subjected to near-infrared radiation; (a1) is an optical image of the artificial scratches on the EP coating of Comparative Example 1 at 0s of NIR irradiation, (a2) is an optical image of the artificial scratches on the EP coating of Comparative Example 1 at 10s of NIR irradiation, (a3) is an optical image of the artificial scratches on the EP coating of Comparative Example 1 at 90s of NIR irradiation, (b1) is an optical image of the artificial scratches on the MXene@EVA / EP coating of Example 1 at 0s of NIR irradiation, (b2) is an optical image of the artificial scratches on the MXene@EVA / EP coating of Example 1 at 10s of NIR irradiation, (b3) is an optical image of the artificial scratches on the MXene@EVA / EP coating of Example 1 at 90s of NIR irradiation, and (c1) is (c2) is the laser confocal image of the artificial scratches on the MXene@EVA / EP coating of Example 1 at 0s of NIR irradiation, (c3) is the laser confocal image of the artificial scratches on the MXene@EVA / EP coating of Example 1 at 90s of NIR irradiation, (d1) is the cross-sectional profile of the artificial scratches on the MXene@EVA / EP coating of Example 1 at 0s of infrared (NIR) irradiation, (d2) is the cross-sectional profile of the artificial scratches on the MXene@EVA / EP coating of Example 1 at 10s of NIR irradiation, and (d3) is the cross-sectional profile of the artificial scratches on the MXene@EVA / EP coating of Example 1 at 90s of NIR irradiation.
[0031] Figure 4 It is a schematic diagram of the self-repair mechanism of the photothermal responsive self-healing coating of Example 1 of the present invention. DETAILED DESCRIPTION
[0032] It should be noted that the following detailed descriptions are exemplary and are intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.
[0033] Unless otherwise defined, all professional and scientific terms used herein have the same meanings as those familiar to those skilled in the art. The reagents or raw materials used in the present invention can be purchased through conventional channels. Unless otherwise specified, the reagents or raw materials used in the present invention are used in a conventional manner in the art or in accordance with the product instructions. In addition, any method and material similar to or equivalent to the described content can be applied to the method of the present invention. The preferred implementation methods and materials described in the text are for demonstration purposes only.
[0034] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit exemplary embodiments according to the present invention. As used herein, unless the context clearly indicates otherwise, the singular form is also intended to include the plural form. In addition, it should be understood that when the terms "comprising" and / or "including" are used in this specification, it indicates the presence of features, steps, operations, devices, components and / or combinations thereof.
[0035] The pharmaceutical agents or raw materials used in the following examples include:
[0036] EVA copolymer refers to ethylene-vinyl acetate copolymer, which is a general polymer with the molecular formula (C2H4) x ·(C4H6O2) y .
[0037] Chloroform, chemical formula CHCl3, is an organic solvent, CAS number: 67-66-3.
[0038] Sodium dodecyl sulfate is an organic compound with the chemical formula C 12 H 25 SO4Na is an anionic surfactant.
[0039] MXene refers to transition metal carbon / nitride two-dimensional nanolayered materials.
[0040] DMF refers to N,N-dimethylformamide, CAS number: 68-12-2.
[0041] PPGDGE refers to polypropylene glycol diglycidyl ether, CAS number: 26142-30-3.
[0042] Example 1
[0043] A photothermal response self-healing coating, the preparation method of which comprises the following steps.
[0044] S1. Dissolve 0.3 g of an EVA copolymer having a melting temperature of 70° C. in 5 mL of chloroform, and perform ultrasonic treatment for 10 min to form a polymer solution having a concentration of 60 mg / mL. Slowly drip the polymer solution into 100 mL of an aqueous solution of sodium dodecyl sulfate (0.5 wt%), and continue stirring at a stirring speed of 1000 rpm at room temperature for 24 h until the chloroform is completely evaporated to form EVA microspheres. Filter the dispersion containing the EVA microspheres, and wash 5 times with deionized water to remove impurities. Then, dry the EVA microspheres at room temperature for further use.
[0045] S2. Disperse 0.2 g of Ti3C2 in MXene material in 50 mL of deionized water and ultrasonically disperse it for 10 min to obtain a first mixed solution with a concentration of 4 mg / mL; disperse 0.1 g of EVA microspheres in 50 mL of DMF and ultrasonically disperse it at room temperature for 10 min to obtain a second mixed solution with a concentration of 2 mg / mL; mix all the first mixed solution with all the second mixed solution and stir at 500 rpm for 24 h, then filter the product, wash it 5 times and dry it at room temperature to obtain MXene@EVA material.
[0046] S3. After mixing 31.4 parts by mass of MU-628 epoxy waterborne resin, 7.6 parts by mass of PPGDGE and 11.5 parts by mass of curing agent polyetheramine, 1 part by mass of MXene@EVA material was added under continuous stirring, and after being evenly dispersed by ultrasonic dispersion treatment, the viscous mixture was placed in a vacuum oven and evacuated for 10 minutes to remove bubbles generated during the preparation process to obtain a bubble-free coating; the coating was applied to the surface of a Q235 carbon steel substrate and cured at 25±2°C for 48 hours to obtain a MXene@EVA / EP coating, i.e., a photothermal responsive self-healing coating.
[0047] The thickness of the prepared MXene@EVA / EP coating is 80 μm.
[0048] Example 2
[0049] A photothermal response self-healing coating, the preparation method of which comprises the following steps.
[0050] S1. Dissolve 0.3 g of an EVA copolymer having a melting temperature of 70° C. in 10 mL of chloroform, and perform ultrasonic treatment for 10 min to form a polymer solution having a concentration of 30 mg / mL. Slowly drip the polymer solution into 100 mL of an aqueous solution of sodium dodecyl sulfate (0.5 wt%), and continue stirring at a stirring speed of 1000 rpm for 36 h at room temperature until the chloroform is completely evaporated to form EVA microspheres. Filter the dispersion containing the EVA microspheres, and wash 5 times with deionized water to remove impurities. Then, dry the EVA microspheres at room temperature for further use.
[0051] S2. Disperse 0.2 g of Ti3C2 in MXene material in 50 mL of deionized water and ultrasonically disperse for 10 min to obtain a first mixed solution; disperse 0.1 g of EVA microspheres in 50 mL of DMF and ultrasonically disperse at room temperature for 10 min to obtain a second mixed solution; mix all the first mixed solution with all the second mixed solution and stir at 500 rpm for 24 h, then filter the product, wash it 5 times and dry it at room temperature to obtain MXene@EVA material.
[0052] S3. After mixing 31.4 parts by mass of MU-628 epoxy waterborne resin, 7.6 parts by mass of PPGDGE and 11.5 parts by mass of curing agent polyetheramine, 3 parts by mass of MXene@EVA material are added under continuous stirring, and after being evenly dispersed by ultrasonic dispersion treatment, the viscous mixture is placed in a vacuum oven and evacuated for 10 minutes to remove bubbles generated during the preparation process to obtain a bubble-free coating; the coating is applied to the surface of a Q235 carbon steel substrate and cured at 25±2°C for 48 hours to obtain a MXene@EVA / EP coating, i.e., a photothermal responsive self-healing coating.
[0053] The thickness of the prepared MXene@EVA / EP coating is 80 μm.
[0054] Example 3
[0055] A photothermal response self-healing coating, the preparation method of which comprises the following steps.
[0056] S1. Dissolve 0.3 g of an EVA copolymer having a melting temperature of 70° C. in 20 mL of chloroform, and perform ultrasonic treatment for 10 min to form a polymer solution having a concentration of 15 mg / mL. Slowly drip the polymer solution into 100 mL of an aqueous solution of sodium dodecyl sulfate (0.5 wt%), and continue stirring at a stirring speed of 1000 rpm at room temperature for 48 h until the chloroform is completely evaporated to form EVA microspheres. Filter the dispersion containing the EVA microspheres, and wash them 5 times with deionized water to remove impurities. Then, dry the EVA microspheres at room temperature for further use.
[0057] S2. Disperse 0.1 g of Ti3C2 in MXene material in 50 mL of deionized water, and ultrasonically disperse it for 10 min to obtain a first mixed solution with a concentration of 2 mg / mL; disperse 0.1 g of EVA microspheres in 50 mL of DMF, and ultrasonically disperse it at room temperature for 10 min to obtain a second mixed solution with a concentration of 2 mg / mL; mix all the first mixed solution with all the second mixed solution and stir at 500 rpm for 24 h, then filter the product, wash it 5 times, and dry it at room temperature to obtain MXene@EVA material.
[0058] S3. After mixing 31.4 parts by mass of MU-628 epoxy waterborne resin, 7.6 parts by mass of PPGDGE and 11.5 parts by mass of curing agent polyetheramine, 5 parts by mass of MXene@EVA material are added under continuous stirring, and after being evenly dispersed by ultrasonic dispersion treatment, the viscous mixture is placed in a vacuum oven and evacuated for 10 minutes to remove bubbles generated during the preparation process to obtain a bubble-free coating; the coating is applied to the surface of a Q235 carbon steel substrate and cured at 25±2°C for 48 hours to obtain a MXene@EVA / EP coating, i.e., a photothermal responsive self-healing coating.
[0059] The thickness of the prepared MXene@EVA / EP coating is 80 μm.
[0060] Comparative Example 1
[0061] A coating, the preparation method of which comprises the following steps.
[0062] S1. Dissolve 0.3 g of an EVA copolymer having a melting temperature of 70° C. in 20 mL of chloroform, and perform ultrasonic treatment for 10 min to form a polymer solution. Slowly drop the polymer solution into 100 mL of an aqueous solution of sodium dodecyl sulfate (0.5 wt%), and continue stirring at a stirring speed of 1000 rpm for 48 h at room temperature until the chloroform is completely evaporated to form EVA microspheres. Filter the dispersion containing the EVA microspheres, and wash them with deionized water 5 times to remove impurities. Then, dry the EVA microspheres at room temperature for further use.
[0063] S2. After mixing 31.4 parts by mass of MU-628 epoxy water-based resin, 7.6 parts by mass of PPGDGE and 11.5 parts by mass of curing agent polyetheramine, 5 parts by mass of EVA microspheres were added under continuous stirring, and the mixture was evenly dispersed by ultrasonic dispersion treatment. In order to remove bubbles generated during the preparation process, the viscous mixture was placed in a vacuum oven and evacuated for 10 minutes to obtain a bubble-free coating; the coating was applied to the surface of a Q235 carbon steel substrate, and cured at 25±2°C for 48 hours to obtain an EP coating.
[0064] The thickness of the prepared EP coating is 80 μm.
[0065] Test example
[0066] The EVA microspheres obtained in step S1 of Example 1 were observed by scanning electron microscopy, and the image is as follows: Figure 1 The MXene@EVA material obtained in step S2 of Example 1 was observed by scanning electron microscopy, and the image is as follows Figure 1 As shown in (b) in the figure, it can be seen that: (the polymerization degree of EVA microspheres is low, and the size is about 60μm; in the MXene@EVA material, the size of the EVA microspheres remains unchanged, while the MXene material is attached to the surface, and the MXene material is in the form of flakes with a size range of 2 to 10μm.
[0067] The EP coating in Comparative Example 1 and the MXene@EVA / EP coating in Example 1 were irradiated with near-infrared light, and the temperature change process was recorded with a thermal imager. Near-infrared light uses highly concentrated laser light, which can effectively focus on a specified area. The results are shown in Figure 2. Figure 2As shown: In the figure, the light yellow area indicates "on", that is, it is irradiated by the near-infrared laser, and the light blue area "off" indicates that it is not irradiated by the near-infrared laser. In the figure, the near-infrared light is irradiated for a total of 5 cycles, corresponding to 5 heating and cooling processes; the MXene@EVA / EP coating exhibits a high time-varying thermal effect and photothermal conversion stability, and exhibits similar photothermal performance during multiple cycles of near-infrared laser irradiation and natural cooling, indicating the stability of photothermal conversion efficiency and the possibility of multiple healing; the near-infrared laser causes the temperature of the composite coating to rise rapidly, rising to 96.6°C after 40 seconds of irradiation; according to previous reports, this temperature is much higher than the T of the EP matrix in the coating. g (glass transition temperature) and T of MXene@EVA microspheres dispersed in the coating m (melting temperature, also known as melting point). Therefore, this condition can fully meet the starting conditions for achieving the self-healing effect. In contrast, Figure 2 Since the EP coating in Comparative Example 1 does not have a photothermal conversion agent, the coating temperature is substantially consistent with the ambient temperature under the cyclic irradiation of the near-infrared laser, and thus has no self-healing ability.
[0068] The self-healing properties of the coating were also tested. The testing process included making artificial scratches with a width of 10 μm and a depth reaching the substrate on the coating surface, and then using a highly concentrated near-infrared laser (power density 0.8 W / cm 2 ) continuously irradiates the scratch area for different set time periods, and the obtained samples are observed under a metallographic microscope and an atomic force microscope (AFM) to obtain relevant information on the scratch width and depth.
[0069] like Figure 3 As shown in (a1) to (a3), no healing performance was observed in the EP coating of Comparative Example 3 during the entire irradiation process of near-infrared light (in the time range of 0s to 90s).
[0070] like Figure 3 As shown in (b1), the width of the artificial scratches on the MXene@EVA / EP coating of Example 1 before irradiation is Figure 3 The artificial scratches in Comparative Example 1 have the same appearance. After 10 seconds of irradiation, the scratches began to heal gradually ( Figure 3 In (b2), melting deformation occurs on both sides of the scratch, which is attributed to the fact that the temperature near the scratch is higher than T g The shape memory function of epoxy resin was brought into play. As the irradiation time increased, the melted EVA microspheres further filled the scratches, reducing the width and depth of the scratches at the same time. After 90 seconds of irradiation, the scratches began to gradually heal. Figure 3 These phenomena can be attributed to the synergistic interaction between the entropy change of the epoxy network and the phase transition of the EVA copolymer. Figure 4 As shown, the T g The introduction of artificial scratches can squeeze part of the epoxy network in the lateral direction perpendicular to the scratch, resulting in a sudden change in the entropy of the system around the scratch. g The stable cross-linked epoxy network prevents network relaxation from restoring the initial system entropy, resulting in quasi-permanent local entropy and entropy-driven energy storage in the scratch area. MXene@EVA can effectively absorb the energy of near-infrared radiation, thereby increasing the local temperature. When the local temperature is higher than T g When the epoxy network is closed, the relaxation of the epoxy network promotes the release of entropy energy, which is manifested as the separated two sides moving toward the center of the scratch. This healing mechanism can be explained in thermodynamic terms and is defined as "shape memory assisted self-healing (SMASH)". However, scratch closure does not represent complete healing of the damage because the broken chain is not completely healed. During the use of the coating in harsh environments, aggressive corrosive substances can penetrate into the coating through tiny scratches, causing corrosion of the metal substrate. Simple closed scratches can only slow down the penetration rate but cannot form a direct barrier. After the introduction of MXene@EVA, the interconnected microspheres melt under near-infrared radiation, further filling the closed scratches and resisting corrosive substances, resulting in excellent self-healing efficiency and recovery of interfacial adhesion strength.
[0071] Figure 3 The laser confocal images of the scratched MXene@EVA / EP in (b1) to (b3) are shown in Figure 2. Figure 3 As shown in (c1) to (c3) in Fig. Figure 3 As shown in (c1) in the figure, there are obvious artificial scratches on the surface of the material before irradiation; Figure 3 As shown in (c2), the artificial scratch indicated by the yellow arrow gradually closed after 10 seconds of irradiation (rising to ~60℃), which is attributed to the shape memory effect; Figure 3 As shown in (c3), after 90 seconds of NIR (near infrared light) irradiation, the scratch was finally filled, which was attributed to the flow of fluid EVA polymer from the matrix to the scratch. Figure 3 (d1)~(d3) show the same Figure 3 The cross-sectional profile size measurement results corresponding to the states shown in (c1) to (c3) show that the scratch depth is also significantly reduced during the effective self-healing process.
[0072] like Figure 4 As shown in Figure 2, for carbon steel coated with MXene@EVA / EP, MXene@EVA microspheres can quickly obtain near-infrared energy and convert it into heat, resulting in a local temperature at the artificial scratch higher than T g. The increased temperature leads to the release of stored entropy energy due to the introduction of scratches. It exhibits rapid network relaxation and closure on both sides of the damage, achieving scratch closure under near-infrared activation. At the same time, the EVA copolymer melts at 90°C, further filling and narrowing the scratches, completely healing the microgaps, and improving the interfacial adhesion. With the completion of the healing process, the coating barrier is rebuilt to restore its original function. Therefore, under the action of a small amount of Cl element, a large amount of dense and passivated Fe3O4 remains on the steel surface. Moreover, this strategy has the potential to repair scratches multiple times. In addition, when the MXene@EVA microspheres are melted, the MXene two-dimensional nanosheets loaded on the surface of the microspheres can be re-embedded into the healed coating and continue to play the original physical barrier role.
[0073] These findings indicate that near-infrared light can achieve contactless repair of the prepared smart coating, greatly reducing the construction cost in harsh marine environments. The photothermal responsive self-healing coating prepared by the present invention has sufficient self-healing performance and potential for application in harsh marine environments.
[0074] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a photothermal responsive self-healing coating, characterized in that: The following steps are involved: S1, dissolving an EVA copolymer having a melting temperature of 70 to 80° C. in chloroform to form a polymer solution having a concentration of 15 to 60 mg / mL, dripping the polymer solution into an aqueous solution of 0.5 to 1.0 wt % sodium dodecyl sulfate, and continuously stirring until the chloroform evaporates to obtain EVA microspheres; S2, dispersing MXene in water to obtain a first mixed solution with a concentration of 2 to 5 mg / mL, and dispersing EVA microspheres in DMF to obtain a second mixed solution with a concentration of 1 to 4 mg / mL; mixing and stirring the first mixed solution and the second mixed solution in a volume ratio of 1:(1 to 2), and then filtering, washing and drying the product to obtain a MXene@EVA material; S3. After mixing 30 to 40 parts by mass of an aqueous resin, 6 to 9 parts by mass of polypropylene glycol diglycidyl ether and 10 to 15 parts of a curing agent, 1 to 5 parts by mass of MXene@EVA material are added under continuous stirring conditions. After being evenly dispersed, the mixture is coated on the surface of the substrate and cured at 20 to 40°C to obtain a photothermal responsive self-healing coating.
2. The method for preparing the photothermal responsive self-healing coating according to claim 1, characterized in that: In S1, the continuous stirring method is: stirring continuously at a stirring speed of 1000 to 1500 rpm for 24 to 48 hours at room temperature; Optionally, in S1, the aqueous solution of sodium dodecyl sulfate containing EVA microspheres is filtered to obtain EVA microspheres, and the EVA microspheres are washed with deionized water and then dried at room temperature.
3. The method for preparing the photothermal responsive self-healing coating according to claim 1, characterized in that: The MXene is selected from one or more of Ti3C2, V2C and Nb2C.
4. The method for preparing the photothermal responsive self-healing coating according to claim 1, characterized in that: In S2, MXene is ultrasonically dispersed in deionized water for 10 to 15 minutes to obtain a first mixed solution; Optionally, in S2, the EVA microspheres are placed in DMF and ultrasonically dispersed at room temperature for 10 to 30 minutes to obtain a second mixed solution.
5. The method for preparing the photothermal responsive self-healing coating according to claim 1, characterized in that: In S2, after the first mixed solution and the second mixed solution are mixed, stirring is continued at a stirring speed of 500 to 700 rpm for 24 to 48 hours; Optionally, in S2, the drying process is performed at room temperature; Optionally, in S2, the MXene@EVA material obtained is in the form of microspheres with a size of 50 to 80 μm.
6. The method for preparing the photothermal responsive self-healing coating according to claim 1, characterized in that: In S3, MXene@EVA material is added under continuous stirring conditions, and a viscous mixture is obtained after ultrasonic dispersion. The viscous mixture is evacuated for 10 to 15 minutes.
7. The method for preparing the photothermal responsive self-healing coating according to claim 1, characterized in that: In S3, the substrate is a metal substrate, including: one of steel and nonferrous metal.
8. A photothermal responsive self-healing coating prepared by the method for preparing a photothermal responsive self-healing coating as described in any one of claims 1 to 7.
9. The photothermal responsive self-healing coating according to claim 7, characterized in that: The coating thickness is 70 to 100 μm, and MXene@EVA material microspheres with a size of 50 to 80 μm are uniformly dispersed in the coating.
10. A use of a photothermal responsive self-healing coating prepared by the method for preparing a photothermal responsive self-healing coating as claimed in any one of claims 1 to 7 and / or a photothermal responsive self-healing coating as claimed in any one of claims 8 to 9, characterized in that: The applications include: applications in marine environments.
Citation Information
Patent Citations
Water-borne photoresponse self-repairing coating material and preparation method thereof
CN110373087A
Dual self-repairing coating based on titanium nitride photo-thermal response and preparation method thereof
CN111826074A
Preparation method and application of self-healing anticorrosive coating of nano container with photo-thermal response
CN117736632A
Self-repairing and self-early-warning coating based on photo-thermal trigger phase change and preparation method of self-repairing and self-early-warning coating
CN118685093A
Shape memory photo-thermal ice preventing and removing super-hydrophobic material and preparation method thereof
CN119060392A
Cited By
Nano self-repairing coating robot and preparation method thereof
CN120900531A